Democracy as problem solving : civic capacity in communities across the globe - Briggs, Xavier de Souza (MIT Press, 2008)
Case studies from around the world and theoretical discussion show how the capacity to act collectively on local problems can be developed, strengthening democracy while changing social and economic outcomes.